Taxonomy, phylogeny and biogeography of African spurfowls Galliformes, Phasianidae, Phasianinae, Coturnicini: Pternistis spp. (4th May 2019) - Mandiwana-Neudani, Tshifhiwa G; Little, Robin M; Crowe, Timothy M; Bowie, Rauri CK
Abstract : Afro-Asiatic perdicine galliform birds, commonly and inconsistently referred to as francolins, spurfowls and partridges, have contentious taxonomic and phylogenetic histories. In a widely followed monograph, Hall combined two putative monophyletic, but taxonomically unnamed, clades comprising 28 perdicine species known as 'francolins' or fisante in South Africa and 13 additional quail-like species (partridges or patryse ) into a single genus, Francolinus, which was the largest genus within the Galliformes. Furthermore, she partitioned fisante + patryse into eight, also formally unnamed, putative monophyletic 'Groups' and speculated on the phylogenetic affinities of four 'Unplaced' species. We investigate fisante using combined morphological, vocalisation and DNA-based evidence and produce a comprehensive revision of fisante taxonomy and phylogeny, a stable classification system and common terminology, and hypotheses vis-à-vis eco-biogeographical processes that promoted their speciation and cladogenesis. Three of Hall's four Groups of fisante sensu stricto (Montane, Scaly and Vermiculated) are para- or polyphyletic evolutionary grades. Only her Bare-throated Group emerges as monophyletic. We recommend the recognition of only one genus, Pternistis, and the use of 'spurfowl' as its collective common name. The proposed new system recognises 25 species, elevating two of Hall's subspecies ( schuetti and cranchii ) to species level and reduces the number of subspecies taxa from 59 to 16. Several species pairs of spurfowls, most notably P. afer and P. cranchii, hybridise in para/sympatry. At least one Bare-throated spurfowl, P. rufopictus, may be the product of stabilised hybridisation between P. afer and/or P. cranchii and P. leucoscepus, and hybridisation between proto-taxa in the Montane and Scaly grades may undermine nodal support for basal spurfowl clades.